Facile and Rapid Fabrication of Petal-like Hierarchical MnO2 Anchored SWCNTs Composite and its Application in Amperometric Detection of Hydrogen Peroxide. Issue 6 (19th March 2020) - Huang, Zhao-Ning; Zou, Jiao; Yu, Jin-Gang
Abstract : Hydrogen peroxide (H2 O2 ) is a vital analyte, such as an intermediate in biological system and a widely used industrial oxidant. It is of great significance for sensitive and accurate detection of H2 O2 in practical applications. In this study, petal-like hierarchical MnO2 anchored SWCNTs composite was prepared by a facile one-step, template-free hydrothermal method. Field emission scanning electron microscopy (FE-SEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS) were used to observe the surface morphology, crystalline phase and chemical bonding state of MnO2 -SWCNTs composite, respectively. Under the optimum conditions, the as-prepared nonenzymatic sensor (MnO2 -SWCNTs/GCE) showed high sensitivity and selectivity for H2 O2 . The peak current was linearly dependent on the H2 O2 concentration, and a linear calibration curve could be obtained in the H2 O2 concentration range 15.0–2000 μ M. The limit of detection (LOD) was calculated to be 1.0 μ M (signal-to-noise ratio of 3, S/N = 3). The inter-day and intra-day precisions were estimated to be <5.0%. The recoveries of H2 O2 in disinfectant at MnO2 -SWCNTs/GCE were in the range of 96.7%–111.9%, and RSD were 2.15%–7.58%. The results demonstrated MnO2 -SWCNTs/GCE had excellent stability, good reproducibility, and high selectivity. Hence, MnO2 -SWCNTs/GCE can be a potential candidate for the practically quantitative detection of H2 O2 in real samples.